Fiscal Politics - Gaspar, Vitor (International Monetary Fund, 2017)
Two main themes of the book are that (1) politics can distort optimal fiscal policy through elections and through political fragmentation, and (2) rules and institutions can attenuate the negative effects of this dynamic. The book has three parts: part 1 (9 chapters) outlines the problems; part 2 (6 chapters) outlines how institutions and fiscal rules can offer solutions; and part 3 (4 chapters) discusses how multilevel governance frameworks can help.